New data on the distribution of fungus gnats (Diptera: Bolitophilidae, Keroplatidae) in Tyva Republic (Russia, Siberia) - Sh. V. Donchak; E. Yu. Subbotina; Yu. V. Maximova (Acta Biologica Sibirica, 2019)
An annotated list is given and the distribution of 13 species of fungus gnats of the families Bolitophilidae and Keroplatidae, collected from Tuva in Eastern Siberia, is provided. As a result of our study, 11 species were added to the list of fungus gnats of Tuva